The Role of Good Corporate Culture and SelfRegulation in the Virtuous Organization - Rivai, Abdul (International Journal of Psychosocial Rehabilitation, 2019)
This paper investigates the role of good organizational culture together with self-regulation as ways to cultivate the character of members of the organization, emphasizing the process of personal moral character development. To achieve this objective, this paper starts by discussing whistle-blowing practices in some organizations, especially business organizations, that have displayed employees’ courage in speaking up about misconduct in their organizations. Two case studies were employed, both cases in the USA and the UK, in relation to an alert to the necessity for ethical awareness by corporations. From the case studies, this paper found that sometimes an employee’s character can be a bulwark of integrity against an environment of practices that involve wrongdoing, and this can lead employees to feel they have no option but to be whistleblowers if the organization does not fulfil its moral responsibilities. Thus, in this paper, the role or function of good corporate culture in shaping the moral development of employees is discussed in relation to the idea of a virtuous organization. At the end, this paper argues that human excellence through self-regulation can be a basis for good organizational culture by presenting moral conduct.